Optimization of brewing process and quality analysis of Vitis quinquangularis Rehd juice beer - GAN Huiting; YANG Jingjing; HAO Junguang; HOU Hui; PANG Tingcai (Shipin yu jixie)
ObjectiveTo broaden the product form of Vitis quinquangularis Rehd processing, and develop a fruit and vegetable juice beer with Yeniang No. 2 Vitis quinquangularis Rehd juice as raw material.MethodsOn the basis of fixed Monascus rice powder additive concentration of 1.5 g/L, Qindaodahua hop additive concentration of 0.6 g/L and Fruity yeast inoculation amount of 0.4 g/L, the optimization process was studied by single factor test and response surface test with alcohol content, total acid, total polyphenol and sensory score as evaluation indexes.ResultsThe fermentation temperature of 18.0 ℃, the initial wort concentration of 11.09 °P, and the dilution of Vitis quinquangularis Rehd juice of 8.13 mL/100 mL were the best conditions. The obtained Vitis quinquangularis Rehd juice beer was sour and delicious, with harmonious fruit and malty flavors, mellow body, bright red color, sensory score of 90.5, total acid 3.24 mL/100 mL, alcohol 3.6%vol, bitterness value 10.8 BU, polyphenols 0.52 mg/mL. In addition, 17 kinds of amino acids, 18 kinds of organic acids, 9 kinds of monomer phenols and 37 kinds of volatile flavor substances were detected in the Vitis quinquangularis Rehd juice beer.ConclusionThe optimized Vitis quinquangularis Rehd juice beer has more rich and mellow taste than ordinary beer, and the addition of Vitis quinquangularis Rehd juice introduces rich amino acids, organic acids, monomer phenols and volatile flavor substances into beer, which has higher nutritional value.